Si@SnS2–Reduced Graphene Oxide Composite Anodes for High‐Capacity Lithium‐Ion Batteries. Issue 23 (26th November 2019) - Dai, Jinyan; Liao, Jiang; He, Minyi; Yang, Mengmeng; Wu, Kaipeng; Yao, Weitang
Abstract: Invited for this month′s cover is the group of Weitang Yao at the Southwest University of Science and Technology. The image shows that developing low‐cost and high‐energy‐density batteries is important for powering our city. The Si@SnS2 ‐rGO composites are good electrode materials for Li‐ion batteries. The Full Paper itself is available at 10.1002/cssc.201902839 . Abstract : "…high‐performance anode material for rechargeable Li batteries" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.201902839 . View the Front Cover here: 10.1002/cssc.201903073 .